2000
DOI: 10.1677/jme.0.0240109
|View full text |Cite
|
Sign up to set email alerts
|

Acute regulation of the bovine gene for the steroidogenic acute regulatory protein in ovarian theca and adrenocortical cells

Abstract: Upregulation of the steroidogenic acute regulatory protein (StAR) is implicated in the rapid synthesis and secretion of steroidogenic cells to produce steroids in response to stimulation by trophic hormones of the gonadal and stress axes. In the present study, we have assessed the kinetics of both StAR gene transcription and protein biosynthesis in primary cell cultures of bovine adrenocortical and ovarian theca cells, under conditions of acute stimulation by corticotrophin (ACTH) and luteinizing hormone (LH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 32 publications
1
15
1
1
Order By: Relevance
“…It also agrees with the previous data found in the same species, S. aurata, in our laboratory (Rotllant et al 2001, Ganga et al 2006 showing that ACTH caused a rapid increase in cortisol levels in superfused head kidney tissue. In addition, our results on StAR expression correlate with data from mammals showing that acute in vivo or in vitro treatment with ACTH leads to a rapid and significant increase (between 1 and 3 h after the treatment) in StAR mRNA in the adrenals (Ariyoshi et al 1998, Ivell et al 2000, Le Roy et al 2000. The results are also similar to other fish species, such as eel, where Li et al (2003) found that ACTH injection increased StAR mRNA levels 1 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It also agrees with the previous data found in the same species, S. aurata, in our laboratory (Rotllant et al 2001, Ganga et al 2006 showing that ACTH caused a rapid increase in cortisol levels in superfused head kidney tissue. In addition, our results on StAR expression correlate with data from mammals showing that acute in vivo or in vitro treatment with ACTH leads to a rapid and significant increase (between 1 and 3 h after the treatment) in StAR mRNA in the adrenals (Ariyoshi et al 1998, Ivell et al 2000, Le Roy et al 2000. The results are also similar to other fish species, such as eel, where Li et al (2003) found that ACTH injection increased StAR mRNA levels 1 .…”
Section: Discussionsupporting
confidence: 85%
“…In mammals, ACTH induces a rapid increase in corticosteroid synthesis and a longer term chronic cyclic AMP (cAMP)/protein kinase A (PKA)-based response that affects both the transcription and translation of several genes encoding for steroidogenic enzymes (reviewed by Sewer & Waterman 2003). In addition, in mammals a very rapid increase in both StAR mRNA (Fleury et al 1996, Ivell et al 2000, Le Roy et al 2000 and StAR protein (Nishikawa et al 1996; reviewed by Lehoux et al 2003) occurs in response to ACTH. Moreover, plasma cortisol has been found to mirror levels of StAR mRNA (Ariyoshi et al 1998, Le Roy et al 2000 and StAR protein , Nishikawa et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…It was also noted that PMA-responsive elements were likely present within the Ϫ151/Ϫ110 region of the Star promoter. Also, the activity of the Ϫ966/Ϫ1 promoter construct was always lower than those of the Ϫ254/ Ϫ1 or Ϫ151/Ϫ1 constructs, a pattern previously observed [32,33]. This unexplained observation could indicate the presence of an inhibitory element between Ϫ966 and Ϫ254 in the Star promoter.…”
Section: Pma Stimulates Star Gene Transcriptionmentioning
confidence: 50%
“…For brightfield dual IHC, the Vector Red kit was used according to the manufacturer's instructions (Vector Laboratories). All antibodies to steroidogenic enzymes have been reported previ- ously with control data (10,(28)(29)(30)(31)(32)(33)(34)(35)(36). In the current experiments, controls included omission of primary or secondary antibody.…”
Section: Methodsmentioning
confidence: 99%